Effect of Alumina (Al2O3) Particles on The Mechanical Properties of Magnesium (Mg) - Zaid, Hayder Muneam Abed; Abed, Abdul Rahman N.; Hasan, Hala Salman (Al-Nahrain Journal for Engineering Sciences, 2019)
In the present study, magnesium-based composites reinforced with different volume fractions (3, 5, 10, and 15) vol.% of micro sized Al2O3 particulates were fabricated by powder metallurgy technique which involves mixed, compacted and sintered. Powders were mixed by ball milling (without balls) for 6 hours at rotation speed 60 rpm. Then powder was compacted at 550 MPa and sintered at 530?C for 2 hours. Microstructures of sintered composites have been investigated by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) energy dispersive. SEM image of sinter samples exhibit good bonding between the magnesium matrix and the alumina. The microhardness and wear resistance of micro composites has been improved significantly compared to that of pure magnesium. Highest value of microhardness is 97 HV at the volume fraction of 10 vol.% Al2O3.